Mathematical Communication Skills in Middle School: A Study of Eighth-Grade Students in West Timor, Indonesia - Anna Sako Bimolo; Aloisius Loka Son; Eduardus Beo Seso Delvion; Javier García-García (CV. Samuel Manurung and Co, 2025)
This study aims to analyze the mathematical communication skills of grade VIII students of the First Secondary School on the material of Relations and Functions. The method used was qualitative descriptive research with the subjects of 21 students in class VIII-B for the 2024/2025 school year. Data was collected through a description test that included indicators of mathematical communication skills and interviews to deepen the results of the analysis. The results of the study show that students' written mathematical communication skills still vary with a tendency to be in the medium to low category. The indicator expressing mathematical ideas in written and visual form obtained the highest achievement of 76.38%, while the indicator interpreted and evaluated ideas only reached 52.86% and the use of mathematical notation reached 47.62%. High-skill students are able to write mathematical models correctly even though the use of formal terms is not consistent, moderate-skill students tend to provide limited explanations, while low-skill students copy more problems without constructing a proper mathematical model. These findings indicate the need for a learning strategy that emphasizes written mathematical communication exercises in a more orderly manner, both in the form of sentences, tables, graphs, and symbols to improve the quality of students' understanding of concepts